Thriving rough sets : 10th anniversary -- honoring Professor Zdzisław Pawlak's life and legacy & 35 years of rough sets - Pawlak, Zdzisław; Wang, Guoyin; Skowron, Andrzej; Yao, Yiyu; Ślęzak, Dominik; Polkowski, Lech (Springer, 2017)
This special book is dedicated to the memory of Professor Zdzisław Pawlak, the father of rough set theory, in order to commemorate both the 10th anniversary of his passing and 35 years of rough set theory. The book consists of 20 chapters distributed into four sections, which focus in turn on a historical review of Professor Zdzisław Pawlak and rough set theory; a review of the theory of rough sets; the state of the art of rough set theory; and major developments in rough set based data mining approaches. Apart from Professor Pawlak's contributions to rough set theory, other areas he was interested in are also included. Moreover, recent theoretical studies and advances in applications are also presented. The book will offer a useful guide for researchers in Knowledge Engineering and Data Mining by suggesting new approaches to solving the problems they encounter.
Keywords: Rough sets.; elektronické knihy; electronic books